Nineteenth-century communications
1 online resource
Keywords: This volume focuses on the development of mail services between ca. 1780 and 1860. It takes as its starting point John Palmer's proposal to reform the mail coach system in the 1780s. As part of this volume, the following themes and subjects are covered: Mail services prior to the introduction of the penny post, including the rise and fall of the mail coach; correspondence and surveillance during the Napoleonic wars; the emergence of local penny posts; and debates about the franking privileges of Members of Parliament. Campaigns for and against the introduction of Rowland Hill's scheme for penny postage between 1837 and 1840. Cultural responses to, and repercussions of, the introduction of the penny post in 1840. The 1844 letter opening scandal. The development of mail infrastructure from 1840 onward, including the development of rural post routes and the use of the railways for the conveyance of the mail.